2017
DOI: 10.1177/1010428317695032
|View full text |Cite
|
Sign up to set email alerts
|

A new insight on reciprocal relationship between microRNA expression and epigenetic modifications in human lung cancer

Abstract: Lung cancer stands among the leading causes of cancer-related death in the world. Although the molecular network implicated in lung cancer development is extensively revealed, the mortality rate is only slightly improved. MicroRNAs are small, endogenous single-stranded evolutionary conserved non-coding RNAs which involve in a wide variety of biological processes including cell growth, proliferation, metabolism, and differentiation. MicroRNAs, as novel biomarkers, have multiple functions in normal lung tissue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 112 publications
(244 reference statements)
0
11
0
Order By: Relevance
“…miRNAs are crucial messengers of intercellular communication. The extracellular transfer of miRNAs is mediated by either protein transporters such as AGO (argonaute), HDL (high density lipoprotein), or extracellular vesicles (EV), e.g., oncosomes, ectosomes, exosomes, and melanosomes [33,47,48,49,50,51,52]. miRNA aggregation with proteins or encapsulation into EVs protect them from degradation by RNases [34,53,54,55].…”
Section: Biogenesis Function and Extracellular Transport Of Mirnasmentioning
confidence: 99%
“…miRNAs are crucial messengers of intercellular communication. The extracellular transfer of miRNAs is mediated by either protein transporters such as AGO (argonaute), HDL (high density lipoprotein), or extracellular vesicles (EV), e.g., oncosomes, ectosomes, exosomes, and melanosomes [33,47,48,49,50,51,52]. miRNA aggregation with proteins or encapsulation into EVs protect them from degradation by RNases [34,53,54,55].…”
Section: Biogenesis Function and Extracellular Transport Of Mirnasmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non‐coding RNAs that regulate a variety of biological processes by modulating gene expression at the post‐transcriptional level . Increasing evidence suggests that miRNAs play an important role in the control of cancer cell invasion and metastasis . For example, miR‐19 triggers the epithelial–mesenchymal transition of lung cancer cells, which is accompanied by growth inhibition .…”
mentioning
confidence: 99%
“…(10) Increasing evidence suggests that miRNAs play an important role in the control of cancer cell invasion and metastasis. (11)(12)(13) For example, miR-19 triggers the epithelial-mesenchymal transition of lung cancer cells, which is accompanied by growth inhibition. (14) miR-92a promotes the epithelial-mesenchymal transition through activation of the PTEN/PI3K/AKT signaling pathway in non-small-cell lung cancer (NSCLC) metastasis.…”
mentioning
confidence: 99%
“…As discussed earlier, several studies using a range of cell lines have indicated overexpression of numerous miRNAs following treatment with epigenetic drugs [ 111 , 112 , 113 ]. The let-7a-3 locus is hypermethylated in normal human lung tissue, but in some lung adenocarcinomas, it becomes hypomethylated and overexpressed [ 114 ]. miRNA-mediated deregulation of DNMTs has been observed in several cancers.…”
Section: Epigenetic Regulators Of Cancermentioning
confidence: 99%